2020
DOI: 10.48550/arxiv.2007.03329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnesium and silicon in interstellar dust: an X-ray overview

D. Rogantini,
E. Costantini,
S. T. Zeegers
et al.

Abstract: Context. The dense Galactic environment is a large reservoir of interstellar dust. Therefore, this region represents a perfect laboratory to study the properties of the cosmic dust grains. X-rays are the most direct way to detect the interaction of light with dust present in these dense environments. Aims. The interaction between the radiation and the interstellar matter imprints specific absorption features in the X-ray spectrum. We study them with the aim of defining the chemical composition, the crystallini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Rogantini et al (2020) recently analyzed the X-ray spectroscopy of the magnesium and the silicon Kedges for eight bright X-ray binaries, distributed in the neighbourhood of the Galactic center, detected with the High Energy Transmission Grating Spectrometer (HETGS) aboard the Chandra X-Ray Telescope. However, they found that amorphous olivine with a composition of MgFeSiO 4 is the most representative compound along all these lines of sight, at least in the diffuse ISM in the inner regions of the Milky Way within ∼ 5 kpc of the center.6 If Fe is tied up in iron carbides (e.g., Fe 3 C; seeNuth et al 1985), its contribution to the wavelength integral of extinction would be smaller than that of iron oxides.…”
mentioning
confidence: 99%
“…Rogantini et al (2020) recently analyzed the X-ray spectroscopy of the magnesium and the silicon Kedges for eight bright X-ray binaries, distributed in the neighbourhood of the Galactic center, detected with the High Energy Transmission Grating Spectrometer (HETGS) aboard the Chandra X-Ray Telescope. However, they found that amorphous olivine with a composition of MgFeSiO 4 is the most representative compound along all these lines of sight, at least in the diffuse ISM in the inner regions of the Milky Way within ∼ 5 kpc of the center.6 If Fe is tied up in iron carbides (e.g., Fe 3 C; seeNuth et al 1985), its contribution to the wavelength integral of extinction would be smaller than that of iron oxides.…”
mentioning
confidence: 99%